Selection of a Suitable Method for the Preparation of Polymeric Nanoparticles: Multi-Criteria Decision Making Approach - Manikandan Mahalingam; Kannan Krishnamoorthy (Tabriz University of Medical Sciences, 2015)
Purpose: The present study is aimed to select the suitable method for preparation of camptothecin loaded polymeric nanoparticles by utilizing the multi-criteria decision making method. Novel approaches of drug delivery by formulation using nanotechnology are revolutionizing the future of medicine. Recent years have witnessed unprecedented growth of research and application in the area of nanotechnology. Nanoparticles have become an important area of research in the field of drug delivery because they have the ability to deliver a wide range of drug to varying areas of body. Methods: Despite of extensive research and development, polymeric nanoparticles are frequently used to improve the therapeutic effect of drugs. A number of techniques are available for the preparation of polymeric nanoparticles. The Analytical Hierarchy Process (AHP) is a method for decision making, which are derived from individual judgements for qualitative factors, using the pair-wise comparison matrix. In AHP, a decision hierarchy is constructed with a goal, criteria and alternatives. Results: The model uses three main criteria 1) Instrument, 2) Process and Output and 3) Cost. In addition, there are eight sub-criteria's as well as eight alternatives. Pair-wise comparison matrixes are used to obtain the overall priority weight and ranking for the selection of suitable method. Nanoprecipitation technique is the most suitable method for the preparation of camptothecin loaded polymeric nanoparticles with the highest overall priority weight of 0.297 Conclusion: In particular, the result indicates that the priority weights obtained from AHP could be defined as a multiple output for finding out the most suitable method for preparation of camptothecin loaded polymeric nanoparticles.